Effect of solar radiation on Holstein heifers’ physiological variables and grazing behavior - Pereira, Ana Flávia Brunheira; Silva, Mariana Letícia Gil; Oliveira, Evandro Menezes de; Nascimento, Sheila Tavares; Toledo, Juliana Beatriz (Acta Scientiarum. Animal Sciences, 2023)
The objective was to assess the physiological and behavioral variables of pasture-raised Holstein heifers on the basis of their coat color. Eight heifers were used, four with black coat, and four with white coat. In the morning and afternoon periods, their physiological variables were measured, namely respiratory rate (RR, mov min. -1), rectal temperature (TR, ºC), and coat surface temperature (TS, ºC). The behavior analysis considered the site (sun or shade), position (standing or lying down), and activities (idleness, rumination, grazing, and others). The data of the physiological variables were assessed through analysis of variance, and significance, through Tukey’s test at 5%, while behavioral data were assessed using the Chi-squared test (SAS Software). There was a difference for all of the heifers’ physiological variables as a function of coat color (p < 0.0001) and period (p < 0.0001), with black ones showing greater results than white ones as to all physiological variables in the afternoon period (p < 0.0001). Grazing behavior is reduced during the hottest hours of the day. We conclude that solar radiation changes the physiological variables and grazing behavior of pasture-raised Holstein heifers.